Clinical Profile of Patients Undergoing Temporary Transvenous Pacing in a Tertiary Cardiac Care Centre in Nepal - Sharma, Manju; Jha, Sunil C; Sayami, Arun; Gajurel, Ratna M; Poudel, Chandra M; Khanal, Rajaram; Pathak, Surya R; Thapa, Shovit; Adhikari, Suman; Yadav, Vijay (Journal of Institute of Medicine Nepal, 2020)
Introduction Temporary transvenous pacemaker insertion is an emergency lifesaving procedure for patients with hemodynamically unstable and life-threatening bradyarrythmias. The aim of this study was to analyze demographics, indications, route of insertion and complications in patients undergoing temporary transvenous pacemaker implantation.MethodsThis was a retrospective observational study conducted at a tertiary-care center in Nepal. The hospital records of patients who had undergone temporary transvenous pacemaker implantation between July 2015 and June 2019 were reviewed.ResultsA total of 343 patients with mean age of 65.52±16.09 years received temporary transvenous pacing. Out of these 205 (59.8%) were males. Greater proportion of patients were between the age group of 70-80 years (n=76, 22.2%). Hypertension (n=97, 28.3%) was the most common comorbidity noted. The most common indication for temporary pacing was symptomatic complete heart block 165 (59.6%). Total of 288 (84%) patients received permanent pacemakers while 55(16%) had reversible cause so TPI was removed. Right Femoral vein was the most common (99%) venous access site. Among the 343 patients, complications were observed in 29 (8.4%) of cases during and after the temporary transvenous pacemaker insertion. The overall mortality stood low at 2% (n=7).ConclusionTemporary transvenous pacemaker insertion is required in elderly population presenting with bradyarrythmias and occasionally in acute myocardial infarction presenting with bradyarrythmias as complication. Temporary pacemaker insertion was overall a safe procedure with infrequent serious complications; however, strategies to avoid and alleviate such complications (RV perforation) should be sought and implemented.